Publish in the undergraduate, materialization or utopia? - Luis Enrique Jimenez Franco; Claudia Diaz de la Rosa (Universidad de Ciencias Médicas de Granma, 2023)
Recent publication entitled Scientific publication as the final stage of the investigative process written by Pedraza Rodriguez motivated the author to write this letter. The article makes a sublime stratification of the research process and highlights the platforms available to the health sciences students to disseminate their results. However, it is necessary to expose the achievements in the research field regarding undergraduate publications. Scientific activity constitutes a challenge and at the same time an opportunity for the future health professional. This dialectical interrelation dictates notable differences in the acquisition of skills necessary for professional performance; no matter what work is done. It is supported by Resolution No. 15 of the Ministry of Public Health of Cuba and constitutes an intra and extracurricular strategy in the training plans of the Higher Education Centers of Medical Sciences in Cuba.